Republic of Uzbekistan : Interim Poverty Reduction Strategy Paper-Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Joint Staff Advisory Note (JSAN) examines Uzbekistan's Interim Welfare Improvement Strategy Paper (I-WISP) for 2005-10. The I-WISP for 2005-10 is the first comprehensive economic and social strategy document presented by the Uzbek authorities. It builds on several medium-term sectoral strategies, including the Production Localization, National Personnel Training, School Education Development, and Health Care Reform Programs. This JSAN provides guidance to the authorities on priority strategic issues to be addressed as they move forward with the preparation of a full Welfare Improvement Strategy Paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet